2016
DOI: 10.21093/di.v16i1.296
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mind Mapping on EFL Students’ Idea Development in Argumentative Writing across Gender Differences and Learning Styles

Abstract: The purpose of the study was to determine the impact of mind mapping as a strategy in generating ideas before writing on the EFL students' idea development in argumentative writing as perceived from their gender differences and learning styles. By conducting an experimental investigation at university level in Indonesia, two existing TOEFL classes at the State Islamic Studies (STAIN) in Kediri were selected by a lottery to group 1: using linear notes (N=41), and group 2: using mind mapping (N=41). For analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Creating encouragement among students of Indonesia to write is not easy (Nurhayati, 2016). Teaching writing in the context of English as a Foreign Language (EFL) is not an easy task (Ningrum, Latief, and Sulistyo, 2016). As we can see, it's very rare to find people that make writing as their hobby.…”
Section: Introductionmentioning
confidence: 99%
“…Creating encouragement among students of Indonesia to write is not easy (Nurhayati, 2016). Teaching writing in the context of English as a Foreign Language (EFL) is not an easy task (Ningrum, Latief, and Sulistyo, 2016). As we can see, it's very rare to find people that make writing as their hobby.…”
Section: Introductionmentioning
confidence: 99%
“…Within the research carried out by Corkett, Hatt, and Benevides (2011) on 6th grade students it is indicated that the self-efficacies of the female students regarding writing were higher than male students. However in the research carried out on university students by Ningrum, Latief, and Sulistyo (2016) it was determined that there was not a significant difference in terms of gender variable considering learning styles.…”
Section: Discussionmentioning
confidence: 97%
“…As Saed and Al-Omari add on that "it is a comprehensive skill that helps reinforce vocabulary, grammar, thinking, planning, editing, revising, and other elements" (p. 88). For these reasons, writing is considered as a difficult process in EFL teaching and learning (Ningrum, Latief & Sulistyo, 2016). Therefore, advancing the learners' writing abilities is believed to be one of the necessary part of EFL learning process (Ibnian, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For these reasons, institutes, educators, researchers and so on began to investigate recent techniques to boost the EFL learners' language proficiency levels (Hinrichs, 2011). Following these, numerous investigators have examined the instructional approaches, methods, models and so on that might be effective to advance the EFL learners' writing proficiency (Ningrum, Latief & Sulistyo, 2016). Significantly, the majority of the traditional approaches for writing are outdated and do not take into consideration the learners' higher order thinking abilities in the Turkish Cypriot context (Dimililer & Kurt, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%